Cancer Treatment: Inhibition of Cancer Cell Migration by Gold Nanorods: Molecular Mechanisms and Implications for Cancer Therapy (Adv. Funct. Mater. 44/2014). (November 2014) - Zhou, Teng; Yu, Meifang; Zhang, Bo; Wang, Liming; Wu, Xiaochun; Zhou, Hejiang; Du, Yipeng; Hao, Junfeng; Tu, Yaping; Chen, Chunying; Wei, Taotao
<x xml:space="preserve">Abstract</x> A quantitative proteomic analysis by C. Chen, T. Wei, and co‐workers on page 6922 shows that gold nanorods (AuNRs) effectively inhibit the metastatic phenotype of cancer cells by modulating the expression of energy metabolism‐related genes, which might provide a new direction for future investigations of functionalized AuNRs as a nano‐platform for cancer therapy. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>